Children's environmental health based on birth cohort studies of Asia (2) – air pollution, pesticides, and heavy metals - Tsai, Meng-Shan; Chen, Mei-Huei; Lin, Ching-Chun; Liu, Chen-Yu; Chen, Pau-Chung (Environmental research, 2019)
The life style and child raising environment in Asia are quite different compared with Western countries. Besides, the children's environmental threats and difficulties in conducting studies could be different. To address children's environmental health in Asia area, the Birth Cohort Consortium of Asia (BiCCA) was co-established in 2011. We reviewed the mercury, polychlorinated biphenyls, perfluoroalkyl substances, phthalates, and environmental tobacco smoke in pervious based on birth cohort studies in Asia. The aim of this study was to summarize the traditional environmental pollution and the target subjects were also based on the birth cohort in Asia area. Environmental pollutants included air pollutants, pesticides focusing on organochlorine pesticides, diakylphosphates, and pyrethroid, and heavy metals including lead, arsenic, cadmium, manganese, vanadium, and thallium. Fetal growth and pregnancy outcomes, childhood growth and obesity, neurodevelopment and behavioral problems, and allergic disease and immune function were classified to elucidate the children's health effects. In total, 106 studies were selected in this study. The evidences showed air pollution or pesticides may affect growth during infancy or childhood, and associated with neurodevelopmental or behavioral problems. Prenatal exposure to lead or manganese was associated with neurodevelopmental or behavioral problems, while exposure to arsenic or cadmium may influence fetal growth. In addition to the harmonization and international collaboration of birth cohorts in Asia; however, understand the whole picture of exposure scenario and consider more discipline in the research are necessary. •Air pollution, pesticides, and heavy metals were associated with adverse effects on Asia children.•Air pollution and pesticides showed more evidence on children’s growth during infancy or childhood and neurodevelopment.•Lead and manganese reported the impact on children’s neurodevelopment; arsenic or cadmium showed may influence fetal growth.